2014
DOI: 10.1016/j.tecto.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Strain weakening enables continental plate tectonics

Abstract: Much debate exists concerning the strength distribution of the continental lithosphere, how it controls lithosphere-scale strain localization and hence enables plate tectonics. No rheological model proposed to date is comprehensive enough to describe both the weakness of plate boundary and rigid-like behaviour of plate interiors. Here we show that the duality of strength of the lithosphere corresponds to different stages of microstructural evolution. Geological constraints on lithospheric strength and large st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 62 publications
0
46
0
Order By: Relevance
“…References [31,32] postulate that mylonitic shear zones in the crust become continually weaker owing to the rising temperatures within the shear zone. Reference [33][34][35][36][37] argue that faults within crystalline basement become weak because of reaction softening: phyllosilicate-rich mylonites (phyllonites) form from the mechanical breakdown of feldspars, which is followed by a chemical breakdown in the presence of a fluid, or grain-size reduction allowing grain-boundary sliding. Reference [38] report that the crystalline basement in the external parts of the Western Alps deformed in a brittle-ductile regime with distributed shear within spaced shear zones or shear bands that are up to a few hundred meters thick.…”
Section: Geometric Aspects Of Thrust Faultsmentioning
confidence: 99%
“…References [31,32] postulate that mylonitic shear zones in the crust become continually weaker owing to the rising temperatures within the shear zone. Reference [33][34][35][36][37] argue that faults within crystalline basement become weak because of reaction softening: phyllosilicate-rich mylonites (phyllonites) form from the mechanical breakdown of feldspars, which is followed by a chemical breakdown in the presence of a fluid, or grain-size reduction allowing grain-boundary sliding. Reference [38] report that the crystalline basement in the external parts of the Western Alps deformed in a brittle-ductile regime with distributed shear within spaced shear zones or shear bands that are up to a few hundred meters thick.…”
Section: Geometric Aspects Of Thrust Faultsmentioning
confidence: 99%
“…[30.31] postulate that mylonitic shear zones in the crust become continually weaker owing to the rising temperatures within the shear zone. [32][33][34] argue that faults within crystalline basement become weak because of reaction softening: phyllosilicate-rich mylonites (phyllonites) form from the mechanical breakdown of feldspars, which is followed by a chemical breakdown in the presence of a fluid, or grain-size reduction allowing grain-boundary sliding. [35] found that the crystalline basement in the external parts of the Western Alps deformed in a brittle-ductile regime with distributed shear within spaced shear zones or shear bands that are up to a few hundred meters thick.…”
Section: Mechanical Aspects Of Thrust Faultsmentioning
confidence: 99%
“…Upper crustal thickness increases at the location of the pop-down and cold upper crustal material is pushed down at great depths. If such lithospheric swelling continues growing, a gravitational instability (Rayleigh-Taylor) may be triggered (Houseman and Molnar, 1997). As predicted from numerical and analytical models, the descent of cold lithospheric material creates lateral temperature gradients and eventually the heavy lithospheric root is removed by mantle convection.…”
Section: Possible Implications For the Development Of Gravitational Imentioning
confidence: 99%